Problems Associated with the Use of Enteric Coated Tablets, Extended Release Tablets and the Storage of Paediatric Antibiotics at Devdaha Municipality in Nepal - Guragain, Sanjeev; Upadhayay, Namrata (Medical Journal of Eastern Nepal, 2022)
Background Enteric coated tablets and extended release tablets are such kinds of tablets that should not be taken in crushed form. Pharmacists may advise to break or crush such tablets to manage the dose form that may lead therapeutic failure and increase the side effects of it. Further, they may not advise patients for the storage of paediatric antibiotics at 2-8° C. The first objective of our study is to find the knowledge among pharmacists about dispensing enteric coated and extended release tablets. The second objective is to explore the knowledge and practice of pharmacists about the storage of paediatric antibiotics after its reconstitution. Methods This study was community based cross-sectional descriptive study which was carried out in 11 pharmacies of Devdaha Municipality from September 2021 to March 2022. The questionnaire was self-administered and interviewed by the investigator. The collected data were entered in excel and expressed in frequencies. Results Almost all (10) pharmacists did not have knowledge regarding the storage of antibiotic in refrigerator (at 2-8° C) after reconstitution. Very few (4/11) pharmacists have knowledge about not consuming enteric coated tablets and extended release tablets in the crushed form. All pharmacists (11/11) have knowledge that psychiatric drugs must not be sold as OTC (Over The Counter) drugs. Conclusion There is lack of knowledge among pharmacists about the importance of storage of paediatric antibiotics after reconstitution. Further there is lack of knowledge and practice about the proper dispensing of enteric coated and extended release tablets to the patients. However, the positive aspect is that they have knowledge of not selling antibiotics and psychiatric drugs as OTC drugs.